Prevalence of mental disorders, associated co-morbidities, health care knowledge and service utilization in Rwanda - towards a blueprint for promoting mental health care services in low- and middle-income countries? - Yvonne Kayiteshonga; Vincent Sezibera; Lambert Mugabo; Jean Damascène Iyamuremye (BMC, 2022)
Abstract Background In order to respond to the dearth of mental health data in Rwanda where large-scale prevalence studies were not existing, Rwanda Mental Health Survey was conducted to measure the prevalence of mental disorders, associated co-morbidities and knowledge and utilization of mental health services nationwide within Rwanda. Methods This cross-sectional study was conducted between July and August 2018, among the general population, including survivors of the 1994 Genocide against the Tutsi. Participants (14-65 years) completed the Mini-International Neuropsychiatric Interview (Version 7.0.2), sociodemographic and epilepsy-related questionnaires. General population participants were selected first by random sampling of 240 clusters, followed by systematic sampling of 30 households per cluster. Genocide survivors within each cluster were identified using the 2007-2008 Genocide Survivors Census. Results Of 19,110 general survey participants, most were female (n = 11,233; 58.8%). Mental disorders were more prevalent among women (23.2%) than men (16.6%) (p < 0.05). The most prevalent mental disorders were major depressive episode (12.0%), panic disorder (8.1%) and post-traumatic stress disorder (PTSD) (3.6%). Overall, 61.7% had awareness of mental health services while only 5.3% reported to have used existing services. Of the 1271 genocide survivors interviewed, 74.7% (n = 949) were female; prevalence of any mental disorder was 53.3% for women and 48.8% for men. Most prevalent disorders were major depressive episode (35.0%), PTSD (27.9%) and panic disorder (26.8%). Among genocide survivors, 76.2% were aware of availability of mental health services, with 14.1% reported having used mental health services. Conclusions Despite high prevalence of mental disorders among the general population and genocide survivors, utilization of available mental health services was low. A comprehensive approach to mental health is needed for prevention of mental illness and to promote mental healthcare services.